ISLAM A SACRED LAW : What Every Muslim Should Know About The Shari'ah - Feisal Abdul Rauf, author 343044 (Kuala Lumpur : Yayasan Dakwah Islamiah Malaysa (YADIM), 2002)
The aim of this book is to introduce the English reader to usul al-fiqh, the general principles of Islamic jurisprudence. Written in non-specialist, easily comprehenSible language, it summarizes the philosophy of Islamic law underlying and common to the Islamic schools of jurisprudence. Its objective is twofold: one is to show the modern Muslim that the underlying dynamics of most of the issues thought to be new and contemporary have in fact been discussed and addressed by Islamic thinkers and jurists from the earliest times in Islamic history. The second objective is to help modern Muslims bring this understanding to bear upon their real life problems and concerns, so they can follow and examine legal arguments presented for their worthiness, and separate what is essential and central to their faith from that which is nonessential and peripheral.